2019
DOI: 10.1186/s13075-019-2062-0
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronic acid and platelet-rich plasma, a new therapeutic alternative for scleroderma patients: a prospective open-label study

Abstract: BackgroundSystemic sclerosis is a systemic connective tissue disease characterized by endothelium damage, fibrosis, and subsequent atrophy of the skin. Perioral fibrosis produces a characteristic microstomia together with microcheilia, both of which cause severe difficulties and affects patients’ daily life, such as eating and oral hygiene. Since there are no effective and specific therapies, we have aimed at evaluating the response to filler injections of hyaluronic acid together with platelet-rich plasma.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…Further research for long-term follow up is necessary. A recent study (9) suggests that a treatment with injections (hyaluronic acid and platelet-rich plasma) also improve both maximal oral aperture as quality of life. It is noteworthy that these injections require general anesthesia and are invasive procedures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further research for long-term follow up is necessary. A recent study (9) suggests that a treatment with injections (hyaluronic acid and platelet-rich plasma) also improve both maximal oral aperture as quality of life. It is noteworthy that these injections require general anesthesia and are invasive procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Various interventions have been examined. Exercises (5)(6)(7)(8) as well as injection therapy (9) have been suggested to restore or maintain mouth opening and freedom of lip movement to improve patients' quality of life. Several studies have shown that stretching (placing the thumbs in opposite corners of the mouth and pulling outward) and oral augmentation exercises (training with tongue depressors) can increase oral aperture in patients with SSc (5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…In an open trial, 10 female patients (aged 18 to 70 years) were treated with three filler injections of linear, non-cross-linked, mediumhigh molecular weight hyaluronic acid, and platelet-rich plasma at an interval of 15 to 20 days. 42 T A B L E 1 Multicenter trials with HA fillers F I G U R E 1 A, 52-year-old patient with localized fat pads in the lower third of the face and also in the cervical region. Flaccidity is seen in these areas.…”
Section: Filler Injections In Scleroderma Patientsmentioning
confidence: 99%
“…In an open trial, 10 female patients (aged 18 to 70 years) were treated with three filler injections of linear, non‐cross‐linked, medium‐high molecular weight hyaluronic acid, and platelet‐rich plasma at an interval of 15 to 20 days 42 …”
Section: Filler Injections In Scleroderma Patientsmentioning
confidence: 99%
“…Although there are no speci c pharmacological treatments for skin involvement in SSc, many strategies have been tried [17][18][19], such as corticosteroids and immunomodulators [20], UVA phototherapy [21][22][23], topical calcitriol [24] and retinoids [25]. Moreover, several local therapies have also been investigated to guarantee a satisfactory aesthetic and functional result, especially for facial brotic skin changes, such as injection of autologous fat grafting and Platelet-Rich Plasma (PRP) [26,27] or of a combination of adipose-derived stromal cells (ADSCs) in hyaluronic acid (HA) solution [28] or of HA and PRP [29].…”
Section: Introductionmentioning
confidence: 99%